Aplikasi Sampling (Sampah Lingkungan) Pengrajin Sampah Berbasis Web Menggunakan Metode RAD (Rapid Application Development) - Nani Purwati; Fitra Nois Dwitama; Sri Kiswati (Evolusi : Jurnal Sains dan Manajemen, 2021)
In the current era of globalization, the growth of environmental waste is increasing. The presence of waste is one of the problems faced by the community. Garbage is a waste material from human activities that has no use, with a population that continues to increase and exceeds the limit so that the amount of waste which also continues to increase will result in the accumulation of garbage. This opportunity is an opportunity for entrepreneurs who care about the environment to take advantage of waste, especially inorganic waste, by recycling waste. Based on observational data, entrepreneurs who care about the environment or waste recycling have problems in product marketing because they still use an offline system and it is difficult to reach the sale of recycled products to the community besides that it can also be used as education on how to use waste waste. Therefore, website information media is a promotional media that is practical, effective, and efficient in promotion. Through the web, consumers are able to access information quickly according to their respective needs. The software design method used is RAD (Rapid Application Development) with the final result in the form of a web-based sampling application.Keywords: application, sampling, RAD, Rapid Application Development